Monitoring Land Use and Land Cover Changes Using Remote Sensing and GIS Techniques, A Case Study: Kufa and Najaf, Iraq - Hussein, Ali Kadhim; Shiltagh, Ahmed Raheem; Mohammed, Faisel G.; Abojassim, Ali Abid; Jassim, Ali Saeed (Iraqi Journal of Science, 2025)
The rapid expansion of the population is a significant factor in the quick transformation rate of land use and land cover (LULC) in various locations worldwide. This approach led to a substantial exhaustion of natural resources. Consequently, continuous monitoring of LULC alterations has become crucial for efficiently administering natural resources and assessing the consequences of climate change. Land cover change (LULC) is widely recognized as a significant driver of environmental change that can affect human activities. Evaluating LULC change is the most accurate approach to understanding past land use patterns, identifying changes that need assessment, and establishing their substantial influence on urban environmental planning and management. Machine learning methods have become more critical for rapidly and accurately mapping LULC using remote sensing (RS) data. The main reason is the growing demand for LULC estimation in ecosystem services, natural resource management, and environmental management. Hence, assessing and contrasting the efficacy of different machine learning classifiers is crucial to attaining accurate LULC mapping. This study was conducted in the Kufa district using eight images, three from Landsat-8 in 2013, 2016, and 2019, to monitor change detection in LULC. Five classes were obtained: residential buildings, water bodies, orchards, bare lands, and agricultural land from a supervised classification using ERDAS Imagine 2015 connected with Google Earth Pro and ArcGIS 10.8 software. For LULC change detection 2013-2016, residential buildings increased by 4.04 km2 to 0.77% of the total area, and bare lands decreased by 47.08 km2 (10.17 % of Kufa’s area), converted into agricultural lands. The orchard area decreased by 22.29 km2 with a percent of 4.88%, which transfers into agricultural lands, and the latter increased by 67.40 km, which is 14.36 % of the total area. However, for LULC change detection 2016-2019, the bare lands increased by 30.66 km2 to 6.63 % of the total area, while orchards increased by 29.67 km2 with 6.47 % of the total area due to agricultural land converted into orchards. The residential buildings decreased by 20.93 km2, with 4.41% of the total area transferred into agricultural lands. This study output is crucial for environmental scientists, land managers, decision-makers, and urban planners in Al Najaf province.